Effectiveness of a multifactorial context-enhancing functional therapy to promote functional arm use and recovery of stroke survivors: study protocol for a clinical trial. Issue 9 (17th September 2019) - Rajagopalan, Vasanthan; Natarajan, Manikandan; Gorthi, Sankar Prasad; Padickaparambil, Sebastian; Solomon, John M
Abstract : Introduction: After a stroke, 55% of survivors do not regain the ability to completely use their arm in daily life functioning. Currently, evidence-based guidelines recommend functional training for improving the affected hand after stroke. However, promoting an optimal quantity and quality of functional training is influenced by personal and environmental contextual factors. Studies that comprehensively target multiple factors regulating arm use are limited. This study compares the effects of functional training to multifactorial context-enhancing functional training program for improving functional arm use and recovery after stroke. Methods and analysis: This is a protocol for an observer-blinded, two parallel groups, randomised controlled trial. A total of 126 community-dwelling subacute and chronic stroke survivors will be included in the study. A tailor-made multifactorial context-enhancing intervention-incorporating education, environmental enrichment and behaviour change techniques to reinforce functional training will be provided to the experimental group. The functional training group will be provided with functional exercises. The intervention will be delivered for 2 months. The primary outcomes of functional arm use and recovery will be measured using Motor Activity Log, Goal Attainment Scale and Rating of Everyday Arm-use in the Community and Home scale. The secondary outcomes of arm motor impairment and function will be measured using Fugl-Meyer upper limb score, Action Research Arm Test, ABILHAND questionnaire and Stroke Impact Scale. These will be measured at three points in time: before, after 2 months and after 1-month follow-up. The outcome measures will be analysed using one-way analysis of variance and regression analysis will be performed to identify factors limiting optimal task practice. Ethics and dissemination: The study has been approved by the Institutional Ethics Committee of Kasturba Hospital, Manipal, India. Participants will sign a written informed consent prior to participation. The results will be published on completion of the trial and communicated to community-dwelling stroke survivors. Trial registration number: CTRI/2017/10/010108